Pengaruh Pengawasan,Komunikasi,Dan Gaya Kepemimpinan Terhadap Disiplin Kerja Pegawai Pada Kantor Dinas Sumber Daya Air Cipta Karya Dan Tata Ruang Provinsi Sumatera Utara - andika andika (CERED Indonesia Institute, 2021)
This research is related to how the influence of supervision, communication, and leadership style on employee work discipline at the Cipta Karya and Spatial Planning Office of North Sumatra Province.. The population of this study was 175 people with a total sample size of 121 respondents and the data collection technique was carried out by using the Likert-scale questionnaire distribution method and processed by data processor SPSS 16.0 for windows. The results of the study indicate that supervision, communication, and leadership styles have a partially positive and significant effect on work discipline. Then the results of the study show that supervision, communication, and leadership style simultaneously have a positive and significant effect on work discipline with a determination coefficient of 32%.